2015
DOI: 10.1128/mcb.00528-15
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Promotes Aberrant PGC1β Expression To Support Human Colon Tumor Cell Survival

Abstract: A major goal of cancer research is the identification of tumor-specific vulnerabilities that can be exploited for the development of therapies that are selectively toxic to the tumor. We show here that the transcriptional coactivators peroxisome proliferatoractivated receptor gamma coactivator 1␤ (PGC1␤) and estrogen-related receptor ␣ (ERR␣) are aberrantly expressed in human colon cell lines and tumors. With kinase suppressor of Ras 1 (KSR1) depletion as a reference standard, we used functional signature onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(93 citation statements)
references
References 52 publications
(51 reference statements)
6
87
0
Order By: Relevance
“…KSR1 regulates the oncogenic potential of activated Ras (14). Our laboratory has recently shown that KSR1 also promotes anchorageindependent growth and tumor maintenance in human colon tumor cell lines (16 (16,19,44,45), the similarity of siKSR1-and siEPHB4-dependent gene expression signatures suggests that EPHB4 is likely to support colon tumor cell survival similarly to KSR1. EPHB4 expression is elevated in a variety of human cancers, including cancers of the head and neck, prostate, bladder, ovaries, large intestine, lung, brain, pancreas, and esophagus (46)(47)(48)(49)(50)(51)(52)(53)(54).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…KSR1 regulates the oncogenic potential of activated Ras (14). Our laboratory has recently shown that KSR1 also promotes anchorageindependent growth and tumor maintenance in human colon tumor cell lines (16 (16,19,44,45), the similarity of siKSR1-and siEPHB4-dependent gene expression signatures suggests that EPHB4 is likely to support colon tumor cell survival similarly to KSR1. EPHB4 expression is elevated in a variety of human cancers, including cancers of the head and neck, prostate, bladder, ovaries, large intestine, lung, brain, pancreas, and esophagus (46)(47)(48)(49)(50)(51)(52)(53)(54).…”
Section: Resultsmentioning
confidence: 94%
“…The gene expression-based high-throughput screen has been described previously (16,19). The gene expression-based signature measured in the screen is based on six genes (ACSL5, BNIP3L, ALDOC, LOXL2, BNIP3, and NDRG1 genes) that are consistently affected by KSR1 depletion, as well as two housekeeping genes (PPIB and hypoxanthine phosphoribosyltransferase [HPRT] genes) that were included for normalization.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations